PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN VARIABEL PEMODERASI GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI PADA PEMERINTAH DAERAH KABUPATEN LAMONGAN - SARWENDA BIDURI (Jurnal Manajerial, 2018)
The relationship between budget participation and managerial performance represent research area which experienced of many debates. The debate draw enthusiasm to do conduct research return with different samples. The early multiply to research into relation between budget participation and managerial performance had been inconclusive and oftentimes contradictory inconsistent show possibility is existence of contingency variables influencing relation between budget participation and managerial performance. This study empirically examined the relationship between budget participation and managerial performance used contingency approach two contingent variables were investigated, namely leadership style and organizational commitment. Questioners were distributed to 55 managers from PEMKAB Lamongan. The responses from 44 (80%) were analyzed by using simple regression and analyzed with residual approach. The result of this research indicated that relationship budget participation had not an effect on positive significant to managerial performance. The relationship between budget participation with contingency approach (leadership style and organizational commitment) to managerial performance was not significant. This matter indicated that according to both contingency variables the relationship between budget participation and managerial persformance is not represent according to best at PEMKAB Lamongan.